Dampak Framing Hasil Survey Pemilihan Presiden 2024 Mempengaruhi Persepsi Publik - Muhammad Devit; Nanang Ridwan (Jurnal Kajian Ilmiah, 2023)
The political situation in Indonesia, which is heating up as the 2024 Election approaches, has gone through crucial stages scheduled since the end of 2022. Political parties have also maneuverer extensively to secure victory in this political contest. So far, three potential presidential candidates have been declared by their respective endorsing parties, and media coverage is abuzz with discussions on survey results related to the presidential candidates, which serve as compelling content that boosts traffic. Not exempt from the influence are the ownership and media conglomerates in Indonesia, some of which are actively involved in politics. The framing of polling results in news can impact the public's perception of the declared potential presidential candidates. This research employs a qualitative approach with a news analysis method to comprehend how such media coverage influences readers' perceptions. The intriguing findings of this study reveal a contradiction in perception compared to the majority of survey results regarding the presidential candidates.